Economic Impact of Routine Cavity Margins Versus Standard Partial Mastectomy in Breast Cancer Patients: Results of a Randomized Controlled Trial. Issue 1 (January 2017) - Chagpar, Anees B.; Horowitz, Nina R.; Killelea, Brigid K.; Tsangaris, Theodore; Longley, Peter; Grizzle, Sonia; Loftus, Michael; Li, Fangyong; Butler, Meghan; Stavris, Karen; Yao, Xiaopan; Harigopal, Malini; et al.
Abstract : Objective: The aim of the study was to compare costs associated with excision of routine cavity shave margins (CSM) versus standard partial mastectomy (PM) in patients with breast cancer. Background: Excision of CSM reduces re-excision rates by more than 50%. The economic implications of this is, however, unclear. Methods: Between October 21, 2011 and November 25, 2013, 235 women undergoing PM for Stage 0–III breast cancer were randomized to undergo either standard PM ("no shave", n = 116) or have additional CSM taken ("shave", n = 119). Costs from both a payer and a hospital perspective were measured for index surgery and breast cancer surgery–related care through subsequent 90 days. Results: The 2 groups were well-matched in terms of baseline characteristics. Those in the "shave" group had a longer operative time at the initial surgery (median 76 vs 66 min, P < 0.01), but a lower re-excision rate for positive margins (13/119 = 10.9% vs 32/116 = 27.6%, P < 0.01). Actual direct hospital costs associated with operating room time ($1315 vs. $1137, P = 0.03) and pathology costs ($1195 vs $795, P < 0.01) were greater for the initial surgery in patients in the "shave" group. Taking into account the index surgery and the subsequent 90 days, there was no significant difference in cost from either the payer ($10, 476 vs $11, 219, P = 0.40) or hospital perspective ($5090 vs $5116, P = 0.37) between the "shave" and "no shave" groups. Conclusions: Overall costs were not significantly different between the "shave" and "no shave" groups due to significantly fewer reoperative surgeries in the former.